MOTIVATION AND PARTICIPATION EXPERIENCE OF HEALTHY VOLUNTEERS IN THE CLINICAL TRIALS OF BIOEQUIVALENCE IN RUSSIA - I. V. Mareev; I. A. Samykina; M. Y. Kolokoltsova; I. D. Pimenov; M. S. Tomofeev; E. S. Kulikov; I. A. Deev; E. V. Borodulina; O. S. Kobyakova; V. V. Udut (Разработка и регистрация лекарственных средств)
The definition of safety, tolerability and efficacy of drugs is largely related with the results of clinical trials (CTs). Currently, phase I studies, pharmacokinetics and bioequivalence, conducted with the participation of healthy volunteers, are one of the main ways to registering drugs in our country and in the world. Despite this, the question of perception by the subjects of these types of studies remains open to this day. The purpose of this work was to analyze the formation and priorities of the motivational determinant by evaluating the experience of participation of healthy volunteers in CTs. During the study, the factors influencing the decision to participate in bioequivalence studies were analyzed.